Obsidian Lithic Technology, Chaîne Opératoire and Symbolic Meaning in the Northern Hualfín Valley (Northwest Argentina) during Late – Inka Period - Bentivenga, Emiliano (2023)
The main objective of this research is to analyse the lithic technology applied to obsidian, a raw material popular amongst pre-Columbian populations from Northwestern Argentina (NWA) because of its social and symbolic value. The analysed assemblage comes from the archaeological site of Villavil 2 (VV2), located in the Hualfín Valley (Catamarca, Argentina) and distant ca. 100 – 200 kms from the nearest sources of this raw material. VV2 was discovered in 2015 by one of the authors and shows a particular presence of rock art which had not previously been registered in this area. The site was associated to the Late and Inka Period (ca. 10th – 16th centuries C.E.). So far, we suggest that this was a place of temporal, but periodical use that best fits with what we would call a ceremonial space.The assemblage comprises the totality of obsidian elements collected from both superficial and stratigraphic contexts. It was divided into three typological classes: tools (projectile points), flakes with natural sharp edges (FNSE) and waste products (WP). We did not identify the presence of cores. The analysis considered the following variables: knapping methods and techniques, size, amount of cortex, flake type and edge types.At VV2, points are the only retouched tools made of obsidian. They correspond to the triangular unstemmed concave-based type, very common during the Late-Inka Periods, and they were shaped using the perimetral bifacial pressure technique, possibly from flake blanks. FNSEs’ size is small, and they present scarce cortex. On the other hand, the abundance of very small-sized WPs is remarkable. They were found in the same stratigraphic context and attest a complete finish of the points (edge retouch).The results let us infer that the point-shaping tasks were carried out in situ. Moreover, the implemented technology involved both major production efforts and skills, that contrast with those involved in local raw material knapping. It is possible that this curated strategy was not related to the difficulty of accessing this allochthonous material. Instead, these choices could reflect social and symbolic meanings. According to linguistic and ethnohistoric information, the obsidian brightness and transparency are propitiatory to win the favour of the w´akas. Furthermore, in NWA the obsidian long-distance exchange is an ancient pre-Columbian tradition that lasted for a long time. Obtaining obsidian could display the ability of a social group to access distant resources and legitimize their political status. Nevertheless, we cannot forget that this raw material also was very important for making different artefacts for subsistence activities.